Preference for locally grown or imported fruit among the millennial generation in Johor, Malaysia - Terano, Rika; Mohamed, Zainalabidin; Rezai, Golnaz; Hanum, Zakiah (Routledge, 2016)
This study attempts to explore factors influencing the choice of locally grown or imported fruits among young Malaysians. It investigates how consumer preference, socioeconomics, and demographic profiles can affect their choice of which fruit category they pick. Five hundred respondents were interviewed by using a structured questionnaire to collect information related to their fruit preferences and choices. The millennium generation in Malaysia, especially the Malay living in Johor, were surveyed as a representation of future consumers of fruit and their subsequent choices and demand. Factor analysis was carried out on statements regarding consumer preferences on choices of local or imported fruit. Five factors were identified as the outstanding consumer preferences for fruits. Demographic profiles of the respondents such as family size, and dimension of fruit preferences, including country of origin, perceived quality, and environmental concerns, were important factors that affect consumers’ purchasing behavior in choosing locally grown or imported fruits. Logit regression indicated that family size, country of origin product quality, perceived quality, and variety of fruits will likely influence the preferences for fruit among the younger generation.